Diversity Pattern of Swallowtails Butterflies in Okomu National Park Edo State in Nigeria - Cynthia, Ojianwuna Chioma; Udoh, Akpan Akaninyene (European Scientific Journal, ESJ, 2018)
Swallowtail diversity sampling in Okomu National Park was carried between July 2012 and June 2014 using butterfly nets and pollard methods (Pollard, 1977) along 1 km by 0.005 km of eight (8) transects in the various ranges (Igwonwan, Arakhuan, Julius Creek, Babui) of the park. Five hundred and fifty five (551) individuals grouped into two genera of twelve species were collected from the ranges of the park. Four rare species notably: Papilio sosia sosia, Papilio nierus nireus, Papilio garienus and Graphium angolanus (Family: Papilionidae) were observed in the park. Papilio garienus and Graphium angolanus recorded for the first time in the park. Most of the Graphium species confined in large congregations around areas with streams and mud puddling. The MOF transect had the highest diversity and was closely related to the CC transect. While the SHR transect had the lowest diversity (H) and was closely related to GRA transect. Swallowtail butterflies were found throughout the months of sampling and significantly higher (p<0.05) during the rainy seasons compared to the dry seasons. Okomu National Park is rich in Swallowtail butterflies.